ANALISIS RELEVANSI BUKU TEKS GEOGRAFI KELAS X DENGAN KURIKULUM MERDEKA DI SMA NEGERI 3 PADANG - Hakim, Muhammad Lukman; Novio, Rery; khairani, Khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
The main purpose of this research is to identify the relevances of Geography textbook which used at 10th grade in Padang senior high school 3 with element and learning achievement on Merdeka Curriculum. Those textbooks are IPS Geografi textbook and IPS Terpadu textbook. This research is qualitative research with content analysis method. The data source of this research is Geography teacher at Padang Senior High School 3 and Geography textbooks itself. This research also uses observation and document study for the data collecting method. From this research it was IPS Geography textbook scores 99 % (Very relevance) to element and 100 % (Very relevance) to learning achievement. And IPS Terpadu Kemendikbud got 95 % (Very relevance) score to element and score 87 % (Very relevance) to learning achievement.